Compromised Integrity, Burnout, and Intent to Leave the Job in Critical Care Nurses and Physicians. (7th February 2022) - LeClaire, Michele; Poplau, Sara; Linzer, Mark; Brown, Roger; Sinsky, Christine
Abstract : OBJECTIVES: To describe relationships between compromised integrity (CI), burnout, and intent-to-leave (ITL) practice in critical care (CC) and noncritical care (non-CC) nurses and physicians. DESIGN: CC nurses (RNs) and physicians (MDs) from the American Medical Association Coping with COVID survey were matched by gender, race, years in practice, and role with non-CC clinicians to determine likelihood of ITL in relation to burnout and CI. SETTING: U.S. Healthcare organizations; July—December 2020. SUBJECTS: One hundred sixty-five CC RNs and 148 CC MDs ( n = 313) matched with 165 non-CC RNs and 148 non-CC MDs from 83 healthcare organizations. MEASUREMENTS AND MAIN RESULTS: Burnout was measured with a single, validated question that mainly reflects emotional exhaustion (EE), and CI was determined by asking if respondents worried about doing things that compromised their integrity moderately or to a great extent. ITL included those moderately, likely, or definitely, intending to leave. Burnout correlated strongly with CI (tetrachoric r = 0.704 [0.606–0.803]; P < 0.001). Of 626 subjects, 59% experienced burnout, 24% CI, and 33% ITL. CC RNs experienced burnout more often (76%) than non-CC RNs (62%; P < 0.01) and CC MDs (51%; P < 0.001). CI was more frequent in CC RNs (44%) than non-CC RNs (23%) and CC MDs (16%; P < 0.001). In multivariate regressions, CC clinicians experiencing burnout had 50% greater odds of ITL than non-CC clinicians experiencing burnout; odds of ITL were substantially higher (odds ratio, 2.8–3.2) in those with CI regardless of location or burnout. In the ICU, those feeling valued by their organization had one-third the odds of ITL. CONCLUSIONS: Burnout (EE) is high (>50%) among CC RNs and MDs, which may result in losses of CC clinicians while demand rises. Preventing CI independent of burnout may reduce turnover in all settings and especially in ICUs. Feeling valued may promote staff retention.